Speculative and Critical Realism. Issue 3 (1st January 2013) - Assiter, Alison
Abstract: This is a contribution to the debate on speculative realism deriving from the book The Speculative Turn: Continental Materialism and Realism, eds Levi Bryant, Nick Srnicek and Graham Harman (Melbourne: re.press, 2011). It is also in part a response to Fabio Gironi's review article on the subject, 'Between naturalism and rationalism: a new realist landscape' ( Journal of Critical Realism 11(3) 2012: 361-87).